George Steiner ou le comparatiste en tant qu’interprète universel - Álvaro Manuel Machado (Carnets)
George Steiner, who died recently, was born in Paris in 1929 and, throughout his immense work as an essayist, was always very attached to literature and, in general, to French culture. Maître à penser, convinced European, polyglot and scholar, Steiner was a professor of comparative literature at the University of Oxford. A dedicated comparatist, always in search of the “arts of meaning”, he devoted a large part of his research to the study of the function of the reader as an interpreter of the “other”. The starting point for this specifically comparative research is his masterpiece After Babel (1975), in which he deepens the notion of the translator’s function as an interpreter of literary works and foreign cultures over the centuries. The long course of this research extends until 1994, the year of the publication of a specific text on the function of the comparatist entitled, in the French edition of the book No Passion Spent (Essays 1978-1996), “Reading across borders”, inaugural lesson of the first chair of comparative literature at the University of Oxford.